Cyclobutadiene automerization and rotation of ethylene: Energetics of the barriers by using Spin‐polarized wave functions. Issue 18 (10th May 2014) - San‐Fabián, Emilio; Moscardó, Federico
<x xml:space="preserve">Abstract</x> Spin‐projected spin polarized Møller–Plesset and spin polarized coupled clusters calculations have been made to estimate the cyclobutadiene automerization, the ethylene torsion barriers in their ground state, and the gap between the singlet and triplet states of ethylene. The results have been obtained optimizing the geometries at MP4 and/or CCSD levels, by an extensive Gaussian basis set. A comparative analysis with more complex calculations, up to MP5 and CCSDTQP, together with others from the literature, have also been made, showing the efficacy of using spin‐polarized wave functions as a reference wave function for Møller–Plesset and coupled clusters calculations, in such problems. © 2014 Wiley Periodicals, Inc.